MEASUREMENT OF VALIDITY AND RELIABILITY OF CUSTOMER SATISFACTION QUESTIONER in E-BOARDING APPICATIONS - Safitri, Sisilia Thya; Kusumawardani, Dwi Mustika; Wiguna, Citra; Supriyadi, Didi; Yulita, Intan (LPPM Universitas Nusa Mandiri, 2020)
PT. Kereta Api Indonesia (Persero) is the largest company in Indonesia which is engaged in railroad transportation. One of the technological innovations carried out by PT KAI (Persero) is to make the KAI Access application with the latest feature is e-boarding. Through the e-boarding feature provided by PT KAI, KAI seeks to provide excellent service to customers. Not many customers use the e-boarding application as a gap between PT KAI's vision and train customers. The gap that exists between the vision and customer acceptance of information technology needs to be measured to determine the extent to which the implementation of the information technology is accepted by the customer. One method used to measure customer satisfaction is to use the use questionnaire. Before measuring customer satisfaction using the Use questionnaire, each item of questions must be tested for validity and reliability. The purpose of measuring the validity and reliability of this research is to ensure the accuracy and reliability of each question on the questionnaire as a test tool. The validity test results used by using the construct validity technique are valid. The reliability test results using the split-half reliability technique have a value of 0.9896 or equivalent to the very high-reliability criteria.